Modern Halal Tourism Transformation towards Sustainability and Innovation through the Implementation of Halal Lifestyle - Yunita Hidayah (Generate Digital Publishing, 2025)
Objective: This research aims to analyse the transformation of modern halal tourism towards sustainability and innovation requires the integration of Maqasid Shariah principles to ensure alignment with Islamic values while addressing supporting and inhibiting factors to achieve a balance between economic, social and environmental goals. Research Design & Methods: This research uses a qualitative approach with a literature review to analyse the drivers, barriers, and application of Maqasid Sharia in modern halal tourism based on data from literature, previous research, industry reports, and related policies. Findings: This study shows that the transformation of halal tourism is driven by government policies, halal lifestyle awareness, and technological innovation, but hampered by a lack of education and infrastructure. The implementation of Maqasid Shariah and innovations such as digitalisation of halal destinations support the sustainability and competitiveness of the sector. Implications & Recommendations: This research recommends collaboration between government, industry, and local communities to overcome halal tourism challenges, increased investment for innovation and sustainable management, implementation of digital technology for efficiency, and training for businesses to understand halal tourism standards. Contribution & Value Added: This research provides insights into the application of Maqasid Shariah principles in building sustainable and innovative halal tourism, and offers strategic recommendations to improve the competitiveness of this sector in the context of global sustainable development.